2021
DOI: 10.1002/ana.26042
|View full text |Cite
|
Sign up to set email alerts
|

Endosome Dysregulation in Down Syndrome: A Potential Contributor to Alzheimer Disease Pathology

Abstract: Intracellular protein trafficking via the endosomes plays a key role in the maintenance of normal neuronal function. Although many diseases of the central nervous system exhibit specific pathological hallmarks, abnormalities of the endosome system are common traits for several of them, including Alzheimer disease (AD). Three main routes originate from the endosomes: the recycling, degradation, and retrograde pathways. Studies have shown that the majority of Down syndrome subjects develop AD pathology and manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…As such, retromer has emerged as a key player in protein trafficking and homeostasis, and its dysfunction is implicated in several neurodegenerative diseases. 16 We recently reported that protein levels of the retromer recognition core, VPS35, VPS26, and VPS29, are decreased and negatively correlate with the amount of brain amyloidosis in patients with Down syndrome. 8 In the present study, we extend this analysis to include tau pathology in the same cohort.…”
Section: Discussionmentioning
confidence: 95%
“…As such, retromer has emerged as a key player in protein trafficking and homeostasis, and its dysfunction is implicated in several neurodegenerative diseases. 16 We recently reported that protein levels of the retromer recognition core, VPS35, VPS26, and VPS29, are decreased and negatively correlate with the amount of brain amyloidosis in patients with Down syndrome. 8 In the present study, we extend this analysis to include tau pathology in the same cohort.…”
Section: Discussionmentioning
confidence: 95%
“…A dysfunction of retromer is also suggested in Down syndrome (DS) [ 19 ]. Individuals with DS have an increased risk of developing AD: more than 60% of individuals with DS will show clinical features of AD by 40 to 50 years of age [ 20 ].…”
Section: Human Disorders Associated With Retromer Dysfunctionmentioning
confidence: 99%
“…However, use of another γ-secretase inhibitor in the same model was thought to improve cognition and neuron loss via an alternative mechanism by modulating the Sonic-hedgehog pathway, which is also altered in DS (Stagni et al, 2017 ). Furthermore, γ-secretase inhibition leads to increased production of CTFs (Netzer et al, 2010 ), which have been implicated in enlargement of endosomes in DS, contributing to perturbed neuronal transport (Filippone and Praticò, 2021 ). Given recent data indicating particularly highly elevated levels of this fragment in people with DS and preclinical DS mouse models (Lana-Elola et al, 2021 ), modulation of γ-secretase in people who have DS should be approached with caution.…”
Section: Pre-clinical Modeling Of Ad-ds: Mechanistic Insightsmentioning
confidence: 99%